Promising New Treatments for Psoriasis. (1st July 2013) - Dubois Declercq, Sarah; Pouliot, Roxane
Abstract : Psoriasis is a chronic, proliferative, and inflammatory skin disease affecting 2-3% of the population and is characterized by red plaques with white scales. Psoriasis is a disease that can affect many aspects of professional and social life. Currently, several treatments are available to help control psoriasis such as methotrexate, ciclosporin, and oral retinoids. However, the available treatments are only able to relieve the symptoms and lives of individuals. The discovery of new immunological factors and a better understanding of psoriasis have turned to the use of immunological pathways and could develop new biological drugs against specific immunological elements that cause psoriasis. Biological drugs are less toxic to the body and more effective than traditional therapies. Thus, they should improve the quality of life of patients with psoriasis. This review describes new psoriasis treatments, which are on the market or currently in clinical trials that are being used to treat moderate-to-severe plaque psoriasis. In addition, this paper describes the characteristics and mechanisms in detail. In general, biological drugs are well tolerated and appear to be an effective alternative to conventional therapies. However, their effectiveness and long-term side effects need to be further researched.